Observation and characterization of the smallest borospherene, B28(-) and B28 - Wang, Ying-Jin; Zhao, Ya-Fan; Li, Wei-Li; Jian, Tian; Chen, Qiang; You, Xue-Rui; Ou, Ting; Zhao, Xiao-Yun; Zhai, Hua-Jin; Li, Si-Dian; Li, Jun; Wang, Lai-Sheng (The Journal of chemical physics, 2016)
Free-standing boron nanocages or borospherenes have been observed recently for B40(-) and B40. There is evidence that a family of borospherenes may exist. However, the smallest borospherene is still not known. Here, we report experimental and computational evidence of a seashell-like borospherene cage for B28(-) and B28. Photoelectron spectrum of B28(-) indicated contributions from different isomers. Theoretical calculations showed that the seashell-like B28(-) borospherene is competing for the global minimum with a planar isomer and it is shown to be present in the cluster beam, contributing to the observed photoelectron spectrum. The seashell structure is found to be the global minimum for neutral B28 and the B28(-) cage represents the smallest borospherene observed to date. It is composed of two triangular close-packed B15 sheets, interconnected via the three corners by sharing two boron atoms. The B28 borospherene was found to obey the 2(n + 1)(2) electron-counting rule for spherical aromaticity.